If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -7 = -9 Reorder the terms: -7 + 5x = -9 Solving -7 + 5x = -9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 5x = -9 + 7 Combine like terms: -7 + 7 = 0 0 + 5x = -9 + 7 5x = -9 + 7 Combine like terms: -9 + 7 = -2 5x = -2 Divide each side by '5'. x = -0.4 Simplifying x = -0.4
| 9x-17=5x-9 | | 3x+4+5=35 | | x/15=3/9 | | -19x+122=-12x+73 | | y-7=5(7-10) | | 3p^3+9p^2-210p=0 | | x-4=15.5 | | 10+6=10 | | (2x-20)(x)=5400 | | c+15=49 | | x-8=-0.35 | | 6^q=q/6 | | 9=9j | | -2x-18=-x-12 | | log(21x)-log(7)=5 | | 19=p-10 | | -0.6y+1.3=4.5-0.2y | | 9x+2=152 | | -3x+11=-2x+6 | | 38=y-39 | | -8=5+s | | 22x-43=14x-17 | | 6x^2+14x-4=0 | | y+42=100 | | 1.6=3y+14.5 | | -7x-3x+2=8-8x-8 | | 12+6w=0 | | 18x-120=10x-72 | | 9999999999999999999999999999999999999999999999999999+99999999999999999999999999999999999999999999999999= | | F(X)=(2x-1)(x+3)(x-2) | | p=50-8x+3x^2 | | 4=52/f |